Cannabis use and suicide risk among Gulf War veterans. Issue 5 (28th May 2023) - Grove, Jeremy L.; Kimbrel, Nathan A.; Griffin, Sarah C.; Halverson, Tate; White, Mark A.; Blakey, Shannon M.; Beckham, Jean C.; Dedert, Eric A.; Goldston, David B.; Pugh, Mary J.; Calhoun, Patrick S.
Abstract: Cannabis use has been indicated as a risk factor for suicide in veterans. This study of Gulf War veterans tested the relationship between self-report past year cannabis use and (a) past year suicidal ideation and (b) risk for suicidal behavior. Data were from a national sample ( N  = 1126) of Gulf War veterans. Logistic regression models indicated cannabis use was associated with past year suicidal ideation and elevated risk for suicidal behavior, independent of key covariates. In corroboration with research on other military populations, this study indicates a potentially concerning association between cannabis use and suicide risk in Gulf War veterans.